Systematic literature review: promosi perpustakaan di era digital melalui media sosial - Qurroti A’yunnina; Luthfi Rofifah (Libraria: Jurnal Ilmu Perpustakaan dan Informasi, 2024)
Advancements in technology and the increasing number of social media users have driven libraries to utilize social media as an effective promotional tool. This study aims to describe the use of social media in promoting libraries in Indonesia. By employing the systematic literature review (SLR) method, literature published between 2019 and 2023 and indexed in Google Scholar was analyzed. Four relevant pieces of literature were selected for analysis and synthesis. The results indicate that libraries in Indonesia, such as Universitas Medan Area, Universitas Andalas, UIN Sunan Ampel, and the Library and Archives Service of Southeast Aceh Regency, use various social media platforms like Instagram, Facebook, YouTube, and WhatsApp to disseminate information, attract visitors, and provide interactive services. Social media enables libraries to reach a broader audience at a low cost while offering engaging content in the form of images and videos. Effective promotional strategies involve branding, rewarding followers, and offering online consultations, which help libraries build a strong image and increase user engagement. This article highlights that libraries active on social media can attract more visitors and raise public awareness of available services and collections. Thus, social media promotion strategies can help libraries remain relevant and provide significant added value to their communities.